2005
DOI: 10.1007/s10661-005-1601-0
|View full text |Cite
|
Sign up to set email alerts
|

137Cs-Uptake into Wheat (Triticum Vulgare) Plants from Five Representative Soils of Bangladesh

Abstract: A pot experiment was conducted to study the uptake of 137Cs by wheat grown in five representative soils of Bangladesh having different soil characteristics. Artificial application of 137Cs increased the activity in soils up to 45.9 Bq/kg soil, measured at the end of the harvest of wheat crop. Different plant parts had different ability to accumulate 137Cs. Grains had the least activity and transfer factor, while the highest activity and lowest transfer factor were measured in roots, which restricted translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…clay content, K, organic matter, CEC, pH, exchangeable ions, etc.). Monira et al (2005) reported that cation exchange capacity and calcium in soils influenced positively, while clay minerals, exchangeable K and organic matter, negatively affected the 137 Cs activity concentrations in wheat plants. Two-week-old barley plants grown on a 137 Cs-contaminated sandy soddy-podzolic soil with the application of potassium at four rates and ammonium nitrogen at three rates showed that mineral fertilizers decreased the accumulation of 137 Cs by plants (Kruglov et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…clay content, K, organic matter, CEC, pH, exchangeable ions, etc.). Monira et al (2005) reported that cation exchange capacity and calcium in soils influenced positively, while clay minerals, exchangeable K and organic matter, negatively affected the 137 Cs activity concentrations in wheat plants. Two-week-old barley plants grown on a 137 Cs-contaminated sandy soddy-podzolic soil with the application of potassium at four rates and ammonium nitrogen at three rates showed that mineral fertilizers decreased the accumulation of 137 Cs by plants (Kruglov et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of data have been generated on the behavior of radionuclides in the soils environment and prediction of their transfer in the ecosystem for crops and animals under conditions found in temperate climate zones (Ohlenschlaeger 1991;Beloasova 1994;Nisbet and Woodman 2000;White et al 2003;Zhu and Shaw 2000;Lasat et al 1998). However, very few data are available for radionuclide transfer and uptake in tropical and subtropical ecosystems (Monira et al 2005;Frissel et al 2002;Sachdev et al 2006;Manjaiah et al 2004). Soil contamination with radiocesium has a long-term radiological impact due to its long physical half-life (30 years for 137 Cs and 2 years for 134 Cs) and its high biological availability.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors appear to be of paramount importance in the eventual transfer of radiocesium from soil to plants. Such factors include soil type and properties (CEC, specific sorption properties, and the nature and amount of organic and mineral matter) (Manjaiah et al, 2003;Lembrechts, 1993;Monira et al, 2005), radionuclide interaction with the soil, level of potential sorptioncompetitive species in the soil solution, and type of crop. In addition to the radionuclide fraction available in the soil, the CEC of the soil, the solid-liquid distribution coefficient (K d ) and levels of competitive species (K + and NH 4 + ) for radiocesium can be used for prediction purposes (Absalom et al, 2001;Fuhrmann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of data have been generated for prediction of radionuclide transfer in the ecosystem for crops, animals and conditions found in temperate climate zones (Ohlenschlaeger, 1991;Beloasova, 1994;Nisbet and Woodman, 2000;White et al, 2003;Zhu and Shaw, 2000;Lasat et al, 1998), but very few data are available for radionuclide transfer and uptake in tropical and subtropical ecosystems (Sachdev et al, 1998(Sachdev et al, , 2006Monira et al, 2005;Rahman and Voigt, 2004). Soil contamination with radiocesium has a long-term radiological impact due to its long physical half-life (30 years for 137 Cs and 2 years for 134 Cs) and its high biological availability.…”
Section: Introductionmentioning
confidence: 99%